Anticoagulation control in different ethnic groups receiving vitamin K antagonist therapy for stroke prevention in atrial fibrillation. Issue 192 (August 2020) - Zulkifly, Hanis; Cheli, Paola; Lutchman, Ivana; Bai, Ying; Lip, Gregory Y.H.; Lane, Deirdre A.
Abstract: Background: Efficacy and safety of vitamin K antagonists (VKAs) is optimised in atrial fibrillation (AF) patients when the International Normalised Ratio (INR) is 2.0–3.0. Anticoagulation control comparing different ethnic groups is limited, although epidemiological studies suggest poorer INR control in non-white cohorts. Methods: VKA control was assessed retrospectively by time-in-the-therapeutic range (TTR) (Rosendaal method) and percentage INR-in-range (PINRR) in 991 White, Afro-Caribbean and South-Asian AF patients [overall mean (SD) age 71.6 (9.4) years; 55% male; mean (SD) CHA2 DS2 -VASc score 3.4 (1.6)] over a median (IQR) follow-up of 5.2 (3.2–7.0) years. Results: Compared to Whites, mean (SD) TTR and PINRR were significantly lower in South-Asians [TTR 67.9% vs. 60.5%; PINRR 58.8% vs. 51.6%, respectively] and Afro-Caribbeans [TTR 67.9% vs. 61.3%; PINRR 58.8% vs. 53.1%, respectively], despite similar INR monitoring intensity. Logistic regression revealed non-white ethnicity [OR 2.62; 95% Confidence Interval [CI] (1.67–4.10) and OR 3.47 (1.44–8.34)] and anaemia [OR 1.65 (1.00–2.70) and OR 6.27 (1.89–20.94)] as independent predictors of both TTR and PINRR < 70%, respectively. At follow-up, 329 (33.2%) patients experienced ≥1 major adverse clinical event. Cardiovascular hospitalisation was significantly higher among South-Asians (32.3%) compared to the Whites and Afro-Caribbeans (21.3% vs 25.6% respectively). Conclusions: Ethnic disparities in quality of anticoagulation control are evident, with South-Asians and Afro-Caribbeans having poorer control compared to Whites, despite similar intensity INR monitoring. Non-white ethnicity remained the strongest independent predictor of poor TTR and PINRR. Interventions to improve anticoagulation control need to be implemented, particularly targeting ethnic minority patients. Highlights: Limited evidence has shown poorer anticoagulation control among ethnic minority groups. We investigated anticoagulation control using time in therapeutic range (TTR) in three ethnic groups. Lower TTR and higher cardiovascular hospitalisations was seen in ethnic minority groups Adjustment for other risk factors demonstrated that ethnicity predicts poor TTR